From Culture to Clicks: How Online Marketing Influence Customer Behaviour in Shopee - Rosmelisa Yusof; Muhammad Danish Asmawi Sabri; Muhammad Danial Haikal Mohd Yunus; Muhammad Farhan Mohd Nazarudin; Muhammad Azib Zamri; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2026)
This study examines the influence of online marketing strategies on customer behaviour in Shopee Malaysia, with a focus on social media advertising, price promotion, trust, and customer engagement. A convenience sampling technique was employed to collect data from 200 Shopee users through an online survey distributed via Google Forms. The survey consisted of structured questions based on a five-point Likert scale. Data were analysed using SPSS through descriptive statistics and multiple regression analysis to test the proposed hypotheses. The findings reveal that culturally relevant marketing messages and social media promotions have a significant positive impact on customer engagement and purchase intention. Additionally, perceived trust and promotional attractiveness also enhance customer confidence and repeat purchase behaviour on Shopee. The study concludes that integrating cultural values in online marketing, improving seller reliability, and maintaining transparent promotional strategies are essential for increasing customer loyalty.